Aluminium matrix composites: Processing of matrix from re–melted aluminium wastes in micro–melting station. (February 2019) - Bulei, C; Todor, M P; Kiss, I; Alexa, V
Abstract: This assessment focuses on the composites with metal matrix, the development of these composites having an important innovation in area of materials engineering over the last years, having in view that these type of composites offer several attractive advantages over the traditional engineering materials due to their superior properties. Therefore, the metal matrix composite become economical alternatives to the monolithic alloys due to their improved specific strength, stiffness and wear resistance combined with better physical properties such as low density and low coefficient of thermal expansion. Even though the specific strength of composites is not up to the mark, advantages like low processing cost and ease of processing make them as potential candidates for various innovative applications. In the meantime, the recycling of any waste is as such a worldwide phenomenon. In this context application of aluminium wastes for development of some value added product has been thought of in this work. This paper presents an overview of aluminium matrix composite systems on aspects relating to processing of matrix from re–melted aluminium wastes.